MEDIATION EFFECT OF NOTARY VERIFICATION DALAM PERJANJIAN WARISAN DIGITAL - Henny Saida Flora; edison; Taqyuddin Kadir (PT. Anagata Sembagi Education, 2025)
The advancement of digital technology has transformed various aspects of human life, including the management of digital inheritance comprising assets such as cryptocurrencies, online accounts, and digital intellectual property rights. However, the transfer of digital inheritance often encounters both legal and technical obstacles, particularly in relation to authentication, identity verification, and disputes among heirs. This study aims to explore how notarial verification functions as a mediator in digital inheritance agreements, examining whether such verification can bridge conflicts or enhance legal certainty. The research adopts a normative juridical approach combined with comparative perspectives from religious (Islamic and Christian) and customary law systems to analyze mediation principles and the validity of notarial verification across different legal traditions. The findings reveal that notarial verification plays a significant mediating role by reducing potential disputes over digital inheritance, facilitating consensus among heirs, and reinforcing the certainty of digital inheritance execution— provided that verification procedures and standards are properly regulated. The discussion links these findings to emerging practices of digital notarization and mediation mechanisms in religious and customary law. In conclusion, notarial verification as a mediating instrument holds strategic potential in digital inheritance agreements, particularly when supported by adaptive regulations that accommodate the unique characteristics of digital assets.